Understanding the Discrepancy between the Perceptions and Implementation of Primary English Teachers’ Pedagogical Content Knowledge - Megayanti, Kadek Manik; Utami, I.G.A. Lokita Purnamika; Dewi, Kadek Sintya (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
This study aimed to analyze the perceptions and implementation of Pedagogical Content Knowledge (PCK) of teaching English to young learners by English primary teachers and analyze the consistency between the perceptions and implementation. This study used an embedded mixed method design with qualitative dominant. The sample subjects were 3 English teachers from different schools. The samples and schools were determined by using convenience sampling. Distributing questionnaire, observation, and interview were the main data collection techniques. The results showed the average score of the teachers’ perceptions was 3.6203 and in the interval 3.3335 ≤ M < 4.0005 which categorized high and in a strong qualification. The average frequency of teachers’ implementation was 4.7045 and in the interval 0.329 ≤ M < 5.0795 which categorized very low. Lastly, the consistency between the two showed no consistency between teachers’ perceptions and implementation of PCK. This inconsistency due to personal and institutional challenges faced by the observed teachers such as lack of time, ineffective students’ behavior management, textbook-based teaching material, non-qualified English education background and inadequate school facilities. Implications drawn from the findings regarding efforts on increasing teachers’ professional enthusiasm is discussed.